Edukasi Digital Marketing Bagi Pelaku UMKM - Alem Febri Sonni; Fahira Nurul Ichzza (Jurnal Pengabdian Masyarakat Hasanuddin (JPMH), 2021)
Real-life work education is one of a form of off-campus education to give students a learning experience, such as by living in a community. Students are thus expected to be able to face and address the development problems of the community. The covid-19 pandemic changes all social activity around the world, restricts direct interaction and must provide both physical and social distance, and cannot assemble to prevent the spread of this virus It turns out that from the digital marketing educational videos that have been made, there are still many UMKM  who do not know how to sell their products on digital media.